Understanding the effects of climate change on Elaeidobius kamerunicus (Coleoptera: Curculionidea), an important oil palm pollinator in Malaysia: predicting future distribution for the year 2050 under different climate pathways - Kumara Thevan Krishnan,; Marcela Pimid, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Elaeidobius kamerunicus is an African oil palm weevil that plays a crucial role as the primary pollinator of oil palm trees and is linked to the production of fruit and palm oil. Malaysia's palm oil and related products export earnings reached RM94 billion in 2023, according to the Malaysia Palm Oil Board (MPOB). Climate change poses a potential threat to the E. kamerunicus population in Malaysia, necessitating research to comprehend the impacts of various climate change variables. This project seeks to document the presence of E. kamerunicus, collect current and future climate data, develop a predictive model using MaxEnt software, and assess the model using statistical techniques to forecast the geographical distribution of E. kamerunicus in Malaysia. The habitat distribution of E. kamerunicus was projected for the year 2050 using two typical concentration pathways (RCPs) from global climate models (GCMs), specifically 2.6 and 8.5. The Maxent models generated a satisfactory model forecast of the Area Under the Curve, which was 0.71. Moreover, True Skilled Statistics achieved a rating of 0.84 (acceptable limit >0.5). The model showed a much greater distribution of E. kamerunicus in Peninsular Malaysia than in East Malaysia. The future model under RCP 2.6 indicates a decrease in E. kamerunicus in high distribution areas in Perak, Selangor, Negeri Sembilan, Melaka, northern Johor, and Sabah, while RCP 8.5 reveals that all states in Malaysia exhibit very high and high distribution of E. kamerunicus. Given the expected increase in atmospheric CO2 levels due to climate change, a more thorough evaluation of the long-term effects of elevated atmospheric CO2 on the physiological characteristics of E. kamerunicus is necessary.